Effects of rheological stratification and elasticity of lithosphere on subduction initiation - Katayama, Ikuo; Yoshida, Masaki; Hirauchi, Ken-ichi (Frontiers in Earth Science, 2022)
The breaking and bending of rigid and elastic lithosphere would have been essential for the initiation of plate subduction, although how this occurred is still poorly understood. Here we test effects of rheological stratification and elasticity of lithosphere on subduction initiation, which are possibly resulted from thermal cracking and seawater penetration into the lithosphere. In addition to the strong influence of water on rheological behavior, the material rigidity is also sensitive to the development of crack and fluid saturation. Numerical modeling indicates that water-weakening and a low-rigidity lithosphere are essential for the initiation of plate subduction, and such conditions are likely to have arisen on the early Earth due to extensive thermal contraction of the planet. Our results indicate that the formation of thermal cracks and penetration of seawater play an important role on subduction initiation, and are likely to have operated on planets other than Earth. However, if the ocean is disappeared, fluid penetration is likely to cease and plate tectonics would have stopped due to increasing the strength and rigidity of the lithosphere.